STRENGTHENING HEALTH SYSTEMS: THE INDISPENSABLE CONTRIBUTION OF GENERAL SURGERY TO GLOBAL HEALTH AND HEALTH EQUITY. - DR. B. KISHORE (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
General surgery is increasingly recognized as an indispensable, yet often underutilized, component of robust health systems globally. This review examines how strengthening general surgical capacity is crucial for advancing global health and achieving health equity. Conditions requiring surgical intervention account for a substantial portion of the global burden of disease, contributing to significant mortality and morbidity, particularly in low- and middle-income countries (LMICs) where access remains acutely limited. An estimated 5 billion people lack access to safe, timely, and affordable surgical care, perpetuating cycles of poverty and exacerbating health disparities. This paper synthesizes evidence highlighting general surgery’s foundational role in building resilient health systems across multiple dimensions. It covers its critical contributions to emergency preparedness and trauma care, maternal and child health, cancer control, and the management of infectious disease complications. By integrating essential surgical services into primary care, strengthening referral pathways, and investing in a skilled workforce and infrastructure, health systems can significantly improve population health outcomes. The review underscores the cost-effectiveness of surgical interventions and argues for increased political will and resource allocation to embed general surgery firmly within national health plans and universal health coverage initiatives, ultimately fostering more equitable and effective global health systems.